THE INFLUENCE OF HUMAN FACTOR ON TRAFFIC SAFETY - Vaichiunas, H. (Science and Transport Progress, 2004)
Problems of the influence of the locomotive driver working time length on the safety of railway trains motion are considered in the paper.